Mineral iron affects the development of mandibular gland in Apis mellifera - de Barros, Daniel C. B. [UNESP]; Shinohara, Alex Junji [UNESP]; Camilli, Marcelo P. [UNESP]; Santos, Sérgio A. A. [UNESP]; Justulin, Luis A. [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (Taylor & Francis, 2020)
In this study the effects of inorganic iron (Fe) supplementation on the morphology of mandibular glands in Apis mellifera were investigated. We randomly assigned 12 beehives to four treatment groups (with three hives in each group), as follows: Fe0 (no Fe supplementation), and Fe25, Fe50, and Fe100 (supplemented with 25, 50, and 100 ppm Fe, respectively). Ferrous sulfate heptahydrate (containing 33.10% Fe), diluted in sugar syrup (1:1 water and sugar), was used as the iron source, and the treatment was done for 3 months. The morphology of glands collected from six-day-old nurse bees from each group was analyzed after sectioning them and visualizing the sections under a microscope. The results were compared by ANOVA followed by the Tukey test (P < 0.05). The area and height of the secretory cells of mandibular glands were observed to be significantly reduced. We conclude that the supplementation of inorganic Fein the feed of bees, at concentrations used in this study negatively modulates their development.
Keywords: beekeeping; mandibular gland; mineral supplementation; morphology; nutrition